The secrets of happy families : improve your mornings, rethink family dinner, fight smarter, go out and play, and much more - Feiler, Bruce. 1964- (William Morrow, 2013)
An informative and compelling guide for families to enrich their home life in our age of distraction. Like millions of parents, bestselling author and New York Times family columnist Bruce Feiler felt squeezed between the needs of aging parents and rapidly growing children. Over three years, he traveled across the United States, seeking out the smartest people and the most effective families to assemble a collection of best practices for families today.